Enemies to lovers : a novel - Williams, Laura Jane (Author) (G.P. Putnam's Sons, 2024)
"From international bestselling author Laura Jane Williams, the queen of the "meet cute," comes a riotous, trope lover's dream: an enemies-to-lovers romance with a brother's best friend, set during a summer vacation in Greece"--